Deaf space in Adamorobe : an ethnographic study in a village in Ghana - Kusters, Annelies (Gallaudet University Press, 2015)
Shared signing communities consist of a relatively high number of hereditarily deaf people living together with hearing people in relative isolation. In the United States, Martha's Vineyard gained mythical fame as a paradise for deaf people where everyone signed up until the 19th century. That community disappeared when deaf people left the island, newcomers moved in, married locals, and changed the gene pool. These unique communities still exist, however, one being the Akan village in Ghana called Adamorobe. Annelies Kusters, a deaf anthropologist, traveled to Adamorobe to conduct an ethnographic study of how deaf and hearing people live together in the village. In her new book, Kusters reveals how deaf people in Adamorobe did not live in a social paradise and how they created "deaf spaces" by seeking each other out. Deaf Space in Adamorobe reveals one example of the considerable variation in shared signing communities regarding rates of sign language proficiency and use, deaf people's marriage rates, deaf people's participation in village economies and politics, and the role of deaf education. Kusters describes spaces produced by both deaf and hearing people as a cohesive community where living together is an integral fact of their sociocultural environments. At the same time, Kusters identifies tension points between deaf and hearing perspectives and also between outside perspectives and discourses that originated within the community. Because of these differences and the relatively high number of deaf people in the community, Kusters concludes it is natural that they form deaf spaces within the shared space of the village community.